The impact of variation in renal replacement therapy settings on piperacillin, meropenem, and vancomycin drug clearance in the critically ill: an analysis of published literature and dosing regimens - Jamal, Janattul-Ain; Udy, Andrew A; Lipman, Jeffrey; Roberts, Jason A (Critical care medicine, 2014)
To describe the effect of different renal replacement therapy modalities and settings on the clearance of meropenem, piperacillin, and vancomycin in critically ill patients and to evaluate the frequency with which current dosing regimens achieve therapeutic concentrations. Regression analyses of published pharmacokinetic data. Pubmed was searched for relevant articles published between 1952 and 2013. Original research articles describing the pharmacokinetics of meropenem, piperacillin, and vancomycin in critically ill patients receiving renal replacement therapy. None. Data from 30 studies were analyzed. The mean age of the patient groups involved in studies of meropenem, piperacillin, and vancomycin were 55.3, 60.3, and 56.9 years, respectively. The mean blood and effluent flow rates used for each antibiotic were 151.3 and 33.8 mL/min, 131.8 and 27.3 mL/min, and 189.3 and 35.6 mL/min, respectively, in continuous renal replacement therapy studies. Correlations existed between effluent flow rate in continuous renal replacement therapy and extracorporeal clearance for meropenem (rs = 0.43; p = 0.12), piperacillin (rs = 0.77; p = 0.10), and vancomycin (rs = 0.90; p = 0.08). Current dosing regimens achieved target concentrations for meropenem (89%), piperacillin (83%), and vancomycin (60%) against susceptible pathogens. Effluent flow rate appears to be a reliable predictor of antibiotic clearance in critically ill patients despite significantly altered pharmacokinetics in these patients. Higher dosing regimens maybe required in critically ill patients receiving renal replacement therapy, in the presence of high effluent flow rates and/or the presence of poorly susceptible pathogens, particularly for vancomycin.